1982
DOI: 10.1161/01.res.50.4.554
|View full text |Cite
|
Sign up to set email alerts
|

Differential baroreflex control of heart rate and vascular resistance in rabbits. Relative role of carotid, aortic, and cardiopulmonary baroreceptors.

Abstract: SUMMARY. We assessed the relative roles of aortic (ABR), carotid sinus (CBR), and vagal cardiopulmonary baroreceptors in the reflex control of heart rate and vascular resistance during changes in arterial blood pressure. Injections of phenylephrine (PE) and nitroglycerin (NG) were given intravenously to anesthetized rabbits (chloralose-urethane). Reflex heart rate responses were impaired significantly by denervation (X) of either CBR or ABR. In contrast, reflex vascular responses in the hindlimb (perfused at c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
1
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 44 publications
8
49
1
1
Order By: Relevance
“…Similar findings in the dog were reported by Ito and Scher,7 8 whose chronic denervation experiments suggested that reflex heart rate responses are impaired to a greater extent by aortic baroreflex denervation than by carotid denervation. In contrast, Guo et al 9 have shown that the CBR and ABR exert similar degrees of vagally mediated heart rate control in anesthetized rabbits during PE-induced hypertension. Furthermore, their studies suggested that there was essentially no redundancy of carotid and aortic baroreceptor afferents with regard to activation of vagal neurons, but that there was essentially "total redundancy" of these arterial baroreceptors with respect to inhibition of sympathetic efferent neurons.…”
Section: Discussionmentioning
confidence: 85%
“…Similar findings in the dog were reported by Ito and Scher,7 8 whose chronic denervation experiments suggested that reflex heart rate responses are impaired to a greater extent by aortic baroreflex denervation than by carotid denervation. In contrast, Guo et al 9 have shown that the CBR and ABR exert similar degrees of vagally mediated heart rate control in anesthetized rabbits during PE-induced hypertension. Furthermore, their studies suggested that there was essentially no redundancy of carotid and aortic baroreceptor afferents with regard to activation of vagal neurons, but that there was essentially "total redundancy" of these arterial baroreceptors with respect to inhibition of sympathetic efferent neurons.…”
Section: Discussionmentioning
confidence: 85%
“…Similar findings in the dog were reported by Ito and Scher (2,3) in which chronic denervation experiments suggested that reflex heart rate responses are impaired to a greater extent by aortic baroreflex denervation than by carotid denervation. In contrast, Guo et al (4) have shown the carotid and aortic baroreceptors exert similar degrees of vagally mediated heart rate control in anesthetized rabbits during phenylephrine (PE)-induced' hypertension. Furthermore, their studies suggested that there was essentially no redundancy of carotid and aortic baroreceptor afferents with regard to activation of vagal neurons, but that there was essentially "total redundancy" of these arterial baroreceptors with respect to inhibition of sympathetic efferent neurons.…”
Section: Introductionmentioning
confidence: 92%
“…The relative roles of carotid sinus and aortic baroreceptors in the reflex control of HR and vascular resistance during changes in arterial blood pressure have been investigated by denervation experiments in rabbits. 27 It was shown that reflex heart rate responses to PHE were impaired significantly by denervation of either carotid or aortic baroreceptors. In contrast, reflex vascular responses in the hindlimb (perfused at constant blood flow) were preserved except for a slight impairment of reflex vasoconstriction after aortic baroreceptor denervation.…”
Section: Effect Of Bcbr On Functional Baroreflex Performance During Vmentioning
confidence: 99%